Analysis of the Implementation of Artificial Intelligence (AI)-Based Promotional Media by Micro, Small, and Medium Enterprises (MSMEs) in Enhancing Brand Awareness in the Digital 5.0 Era - Wahyu Fitri; Anggi Hadi Wijaya; Zumiarti Zumiarti (Edumaspul: Jurnal Pendidikan, 2025)
With the increasing use of Artificial Intelligence (AI)–based technology today, this development has become a positive opportunity for Micro, Small, and Medium Enterprises (MSMEs) in Padang City. By utilizing AI, MSME actors can significantly reduce marketing costs when promoting their products. This study aims to analyze the implementation of MSME product promotion media using Artificial Intelligence (AI) as an effort to enhance brand awareness in the digital 5.0 era. As of March 2025, there were 47,289 MSME actors recorded in Padang City, spread across 11 districts. Fundamentally, MSMEs are currently the largest contributors to the national economy. However, literacy and understanding of the use of emerging technologies remain limited among MSME actors. This condition is reinforced by data from 2014 to 2018, which shows that only 46.87% of MSMEs utilized promotional media and internet access. Furthermore, from 2019 to the end of 2021, nearly 90% of MSMEs experienced stagnation due to the spread of the COVID-19 pandemic. Therefore, specific research efforts and targeted actions are needed to examine the implementation of AI-based promotional media to improve the literacy and capabilities of MSME actors. This study employs a mixed-method research design (qualitative–quantitative) with a project-based approach. The research process began with the collection of primary and secondary data through in-depth interviews with 30 informants and the distribution of 476 questionnaires, supported by data from social media, online media, mass media, and other relevant sources. This research integrates interdisciplinary expertise (communication studies, social sciences, and economics) to address the identified problems, resulting in findings that describe MSME needs and implement effective strategies for promoting MSME products, as well as providing policy recommendations and practical suggestions for relevant stakeholders. The expected outcome of this research is one mandatory output in the form of a National Journal indexed in SINTA 1–4, aligned with Technology Readiness Level (TRL) 1, with a final target of TRL 3.